2011
DOI: 10.1080/17533015.2010.525516
|View full text |Cite
|
Sign up to set email alerts
|

Art in a Spanish children's hospital

Abstract: This article aims to present and discuss a case-study of humanization through art applied to a children's hospital. Art is considered herein as a resource to improve hospital environments. The experience related to the improvement of these environments took place in the Children's Emergency Unit of the University Hospital in Salamanca (Spain). After describing the context of the case-study, some attention will be paid to the phases of the process, emphasizing the aspects linked to the care culture of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Developing self-identity and self-expression are an important part of the adolescent phase. 9 As evidenced by studies in other studies, 42,43 young people struggle with self-expression and arts-based interventions may provide a medium for articulating their emotions and concerns.…”
Section: Discussionmentioning
confidence: 95%
“…Developing self-identity and self-expression are an important part of the adolescent phase. 9 As evidenced by studies in other studies, 42,43 young people struggle with self-expression and arts-based interventions may provide a medium for articulating their emotions and concerns.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, increased attention has been afforded to examining the quality of health care environments and the impact such environments have on health and well-being (Fornara et al, 2006; NHS Estates, 2003). It has been argued that positive environmental stimulation and more user-focused humane hospital settings can promote children’s well-being by reducing stress or negative feelings as children endure their daily contact with illness, disease and pain (Belver and Ullan, 2011; Park, 2009). This is compounded by the UK National Service Framework for Children and Young People, which proposed thatcare will be provided in an appropriate location and in an environment that is safe and well-suited to the age and stage of development of the child and young person.…”
Section: Introductionmentioning
confidence: 99%
“…In this block are the following works: Belver and Ullán (2011), Bretler et al (2017), Cartland et al (2018), Ciucci and Heffner-Solimeo (2018), Ho et al (2015), Pati and Nanda (2011), Pearson et al (2019), and Ullán et al (2011). The results of these studies indicated that visual artistic interventions (mainly paintings and drawings but also photographs, murals, or comics) could have a positive impact on some physiological results (Pearson et al, 2019), the level of anxiety experienced (Cartland et al, 2018; Pati & Nanda, 2011), and the parents’ satisfaction (Belver & Ullán, 2011; Bretler et al, 2017; Ullán et al, 2011). Adding explanations to the works of art exhibited in the hospital (Ho et al, 2015) can increase their therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…The first refers to the need to carry out a conjoint work of artistic and scientific/health perspectives. We have grouped the following works under this heading: Belver and Ullán (2011), Capon (2012), and Morgan (2018), those that stress the importance of enhancing multidisciplinary approaches that join health perspectives and artistic perspectives in the design of healthcare spaces. The second topic refers to the description of artistic interventions or experiences in pediatric hospitals.…”
Section: Resultsmentioning
confidence: 99%